Insights into the Daily Life of Le Corbusier: the agendas in the Fondation Le Corbusier - Tim Benton (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The resources available for research at the Fondation Le Corbusier are many and varied. Among these, the agendas (diaries) offer particularly intriguing insights into the public and private life of Le Corbusier. These diaries present a number of difficulties to the researcher: the notes are often difficult to read and even more difficult to interpret. The organisation of the diaries has to be understood. The pages of the diaries are undated. Establishing the approximate dates for each page presents a challenge that can only be overcome by reference to a wide range of other documentation. This paper offers suggestions for how to analyse and interpret this difficult material. With a number of worked examples, an indication is given of some of the insights that can be obtained from mining this data.